2018
DOI: 10.1177/2047487318819142
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone, sex hormone-binding globulin and risk of cardiovascular events: A report from the Outcome Reduction with an Initial Glargine Intervention trial

Abstract: Aims: Testosterone and its binding protein sex hormone-binding globulin have been associated with cardiovascular disease and dysglycaemia. However, information on the prognostic implication in patients at high cardiovascular risk with dysglycaemia is inconsistent. The study objective was to determine whether testosterone and/or sex hormone-binding globulin predict cardiovascular events or death in dysglycaemic patients. Methods: Dysglycaemic males at high cardiovascular risk ( n = 5553) who participated in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 133 publications
(239 reference statements)
0
4
0
Order By: Relevance
“… 21 On the one hand, it can specifically bind to sex hormones and participate in their transport. 22 On the other hand, it can regulate the concentration of biologically active sex hormones in the blood. SHBG has high binding power with testosterone.…”
Section: Discussionmentioning
confidence: 99%
“… 21 On the one hand, it can specifically bind to sex hormones and participate in their transport. 22 On the other hand, it can regulate the concentration of biologically active sex hormones in the blood. SHBG has high binding power with testosterone.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Given the limited discriminative ability of these approaches, 3 several additional non-circulating and circulating biomarkers have been examined as means of refining risk stratification, with potentially promising results. 4,5 These biomarkers include high-sensitivity C-reactive protein (hs-CRP), N-terminal pro-brain natriuretic peptide (NT-proBNP), and soluble urokinase plasminogen activator receptor (suPAR). 611 Accordingly, the aim of this study was to examine whether these three circulating biomarkers carried incremental prognostic value in predicting cardiovascular events beyond traditional cardiovascular risk factors in apparently healthy individuals.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a study showed that SHBG could predict cardiovascular events [hazard ratio (HR) = 1.07, 95% CI = 1.00 to 1.14), p = 0.03] and all-cause mortality (HR = 1.13, 95% CI = 1.06 to 1.21, p < 0.01) in males at high risk of CVD. 64 Therefore, we conducted subgroup analyses according to mean or quartile of age and BMI to explore the factors that might influence the difference in SHBG level between the moderate-severe and mild groups. The results showed that when the age was more than 50 years, the SHBG levels of the moderate-severe group were lower than those of the mild group; when the BMI was over 27 kg/m 2 , the SHBG level of the moderate-severe group was higher than that of the mild group.…”
Section: Discussionmentioning
confidence: 99%